Analysis of Student Financial Literation Levels Hamzanwadi University and Its Affecting Factors - Pahrudin, Pahrudin; Hakim, Irma Wahyuni; Shollina, Shollina (Universitas Hamzanwadi, 2018)
The purpose of this study was to determine the description of financial literacy level, to determine whether financial behavior variables influence financial literacy to determine whether financial management variables influence financial literacy and to find out whether Behavior variables and financial management have a simultaneous influence on hamzanwadi university student financial literacy rates. The methodology used in this study is the Research Descriptive Survey and Explanatory Survey. The subject of this study was students of Hamzanwadi University. Analytical techniques used with descriptive analysis and multiple linear regression with t-test. The results showed that the level of student financial literacy is at a low level, namely the results of the descriptive statistics average of 36.93 or the value is in the low category because the value is less than 60. The results showed that financial behavior variables did not affect financial literacy, variables financial management has an effect on financial literacy and behavioral and financial management variables have a simultant effect on student financial literacy. The importance of the results of this study as a form of recommendation that to improve financial literacy among students, it is time to encourage socialization of personal finance education programs into the academic as part of the education system at the University to increase the level of student financial literacy.